Results-based management for climate resilience and mitigation. Examples from South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Researchers from CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) share approaches to Results Based Management. Featuring Dr. Bruce Campbell, Dr. Philip Thornton and Dr. Ana Maria Loboguerrero Rodriguez. The session concludes with a Q&A with webinar participants. Webinar recorded on 23 January 2015.